2016
DOI: 10.1038/nutd.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

A low-carbohydrate high-fat diet increases weight gain and does not improve glucose tolerance, insulin secretion or β-cell mass in NZO mice

Abstract: Background/Objectives:Dietary guidelines for the past 20 years have recommended that dietary fat should be minimized. In contrast, recent studies have suggested that there could be some potential benefits for reducing carbohydrate intake in favor of increased fat. It has also been suggested that low-carbohydrate diets be recommended for people with type 2 diabetes. However, whether such diets can improve glycemic control will likely depend on their ability to improve β-cell function, which has not been studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 55 publications
6
46
0
Order By: Relevance
“…For example, one study stated that "Long-term highfat, low-carbohydrate KD leads to features that are also associated with the metabolic syndrome and an increased risk for type 2 diabetes in humans" [1]. Two other studies reported that "Use of LC-HF diets … should be balanced against potentially harmful metabolic side effects" [2] and that "Our results do not support the recommendation of an LCHFD for use in prediabetes [3]. Moreover, based on that last study, the news media reported to the public that "Following a low-carbohydrate, high-fat diet for just eight weeks can lead to rapid weight gain and health complications, a new mouse study has demonstrated.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…For example, one study stated that "Long-term highfat, low-carbohydrate KD leads to features that are also associated with the metabolic syndrome and an increased risk for type 2 diabetes in humans" [1]. Two other studies reported that "Use of LC-HF diets … should be balanced against potentially harmful metabolic side effects" [2] and that "Our results do not support the recommendation of an LCHFD for use in prediabetes [3]. Moreover, based on that last study, the news media reported to the public that "Following a low-carbohydrate, high-fat diet for just eight weeks can lead to rapid weight gain and health complications, a new mouse study has demonstrated.…”
Section: Introductionmentioning
confidence: 64%
“…It was found that, despite preventing weight gain in mice, the KD induces insulin resistance [37]. In addition, it was later shown that the KD causes glucose intolerance without weight loss in mice [1], and even increases weight gain and glucose intolerance in New Zealand Obese mice [3]. Other studies also reported insulin resistance and glucose intolerance in rodents fed a KD [1,2,[38][39][40][41][42].…”
Section: Self-contradictory Results In Rodentsmentioning
confidence: 99%
“…It should be noted that there are some papers that correlate increased risk of developing glucose intolerance and noninsulin-dependent diabetes mellitus with the LCHF diet [42]. On the other hand, in mice it is already shown in the literature that the LCHF diet is found to increase weight gain and does not improve the glycemic profile [43]. These differences might correlate with the differences of metabolism present in different species.…”
Section: Discussionmentioning
confidence: 99%
“…Low-carbohydrate, high-protein, low-energy diets are widely used in weight management programs. A growing body of evidence suggests that the high-protein, low-carbohydrate diets improve hyperinsulinemia [44]. These results suggest a similar control mechanism of metabolic stores and insulin signaling in both vertebrates and suggest that developmental diets can influence the insulin-signaling mediated life-history traits during adult life, and these affects vary in males and females, suggesting sex-specific differences in nutrient regulation.…”
Section: Discussionmentioning
confidence: 87%